Assessing the impact of credit conditions on household well-being through repayment pressures in Botswana and Zimbabwe. - Musandipa, Costa; Nkala, Peter; Malunguza, Noble; Mbedzi, Edson (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2025)
Amidst tightening global monetary conditions, this study investigates how repayment distress functions as a transmission channel between interest rate fluctuations and household financial well-being (HFWB) in Botswana and Zimbabwe. Drawing on Credit Market Theory, Debt Overhang perspectives, the Financial Accelerator and Financial Stability frameworks, the analysis applies a novel tree-based mediation approach to assess the interplay among borrowing costs, loan performance and human development outcomes. Empirical results reveal a pronounced mediating effect in Botswana (Indirect Effect = -0.0581; R² = 0.963), suggesting that non-performing loans (NPLs) amplify the adverse consequences of rising interest rates for households. Conversely, Zimbabwe exhibits a weaker mediation pathway (Indirect Effect = -0.0000; R² = 0.784), shaped by macroeconomic volatility, hyperinflation and dependence on informal credit markets. These findings underscore the importance of context in shaping credit risk and monetary transmission. Policy implications point to strengthening regulatory oversight and NPL management in Botswana, while in Zimbabwe, macroeconomic stabilization and formal credit deepening are critical. By offering one of the first comparative applications of tree-based mediation modelling in Sub-Saharan Africa, this study contributes new empirical evidence to debates on financial inclusion, household vulnerability and development in low- and middle-income economies.